Air Traffic Law Segmentation in the Era of Industrial Revolution 4.0 Challenges and Solutions Based On Futuristic Legal Perspective - Ai Permanasari; Sirrinawati; Aep Sulaeman; Suarman Gulo (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The Fourth Industrial Revolution (Industry 4.0) has significantly transformed various sectors, including air transportation. Technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and automation have driven innovations like drones and flying cars. In Indonesia, the implementation of flying cars has begun testing in the New Capital (IKN) as part of a transformation towards smarter and environmentally friendly transportation. However, these developments also present challenges in air traffic regulations. Law No. 1 of 2009 on Aviation and its related regulations have not fully accommodated these new technologies. This study examines how air transportation law in the Industry 4.0 era can be analyzed from a futuristic legal perspective and the welfare state theory. The state plays a crucial role in ensuring adaptive regulations, including aspects of safety, privacy, and harmonization with international regulations. This research employs a normative juridical method, relying on literature studies and secondary data analysis. A qualitative descriptive approach is used to analyze regulations relevant to advanced air transportation technology. The research findings indicate that technological advancements such as drones and flying cars necessitate updates in air transportation law. Responsive regulations and adequate infrastructure are essential to ensure that innovations in air transportation can operate safely, efficiently, and inclusively